(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2010)
The purpose of the study was to assess the influence of physiotherapeutic devices on respiratory system function after coronary bypass grafting. The tasks of the study: 1. To assess and compare the factors of the respiratory function on the first group (physiotherapist employed physiotherapy once a day) and in the second group (physiotherapist employed physiotherapy twice a day). 2. To compare the factors of the respiratory function and the frequency of post-operative complications between non-smokers and smokers in the first and the second group. The study included 40 patients after coronary artery bypass grafting in the Cardiac, thoracic and vascular clinic in the hospital of Kaunas University of Medicine. The studied patients were distributed into two equal groups. The first group received physiotherapy once a day; the second group received physiotherapy twice a day. In this study we measured the factors of the respiratory function (the respiratory rate and the Hence sample) on the first and the eighth post-operation days. The patients case-histories provided the data about atelectasis. The patients were inquired whether they smoked during six weeks before the operation. We found that on the sixth day after the operation the values of the indicators of the respiratory function (the respiratory rate and the Hence sample) in the second group were significantly better (p < 0.05) than the values of the analogous indicators in the first group. Consequently it is advisable to apply physiotherapeutic procedures twice a day to the coronary artery bypass grafting patients. Smoking was contributed to development of such post-operative complications as atelectasis. We found that the values of the respiratory function indicators (the respiratory rate and the Hence sample) in non-smokers were significantly (p < 0.05) better than in the patients’ who smoked (p < 0.05). Keywords: ischaemical heart disease, coronary artery bypass grafting, post-operative complications of respiratory function, smoking, physiotherapy